Halal Cart With Sustainable Philanthropy (A Case Study in Bau-Bau City of Southeast Sulawesi, Indonesia) - Insawan, Husain (International Journal of Transdisciplinary Knowledge, 2022)
This study aims to examine: a) the existence of halal cart in Bau-Bau city of Southeast Sulawesi in which the operations are based on the philanthropic awareness of the employees of the Ministry of Religion in Bau-Bau; b) the business effect using halal carts on philanthropic actions of the owners in Bau-Bau; and c) the halal cart model with sustainable philanthropy as the best practice of sharia-based microbusinesses in Southeast Sulawesi. This research is designed with the descriptive-qualitative methods, in which the researchers collected the data by observation, in-depth interviews, and focused-group discussions. Also, the data analysis technique used refers to the Miles and Hubermas theory, namely data display, reduction, and conclusions. The results indicate that that the halal cart is one of the microbusiness models developed by doing small businesses such as the food vendors who meet the halal (hygienic ingredients and tools) and thayyibah (based on the health and hygiene standards) criteria. The halal cart significantly affects the business owner philanthropic actions where they spare their income for the charity in form of infaq. The halal cart model with sustainable philanthropy can be used for all the microbusinesses in Southeast Sulawesi. As far as we know, there is still little research on the halal cart model with a philanthropic perspective as a good practice for sharia-based micro businesses, especially in Muslim communities, this research is an attempt to enrich insights and fill the gap.